Genetic and functional diversity of the multiple lungfish myoglobins. (1st November 2019) - Lüdemann, Julia; Fago, Angela; Falke, Sven; Wisniewsky, Michelle; Schneider, Igor; Fabrizius, Andrej; Burmester, Thorsten
Abstract : It is known that the West African lungfish ( Protopterus annectens ) harbours multiple myoglobin (Mb) genes that are differentially expressed in various tissues and that the Mbs differ in their abilities to confer tolerance towards hypoxia. Here, we show that other lungfish species ( Protopterus dolloi, Protopterus aethiopicus and Lepidosiren paradoxa ) display a similar diversity of Mb genes and have orthologous Mb genes. To investigate the functional diversification of these genes, we studied the structures, O2 binding properties and nitrite reductase enzymatic activities of recombinantly expressed P. annectens Mbs (PanMbs). CD spectroscopy and small‐angle X‐ray scattering revealed the typical globin‐fold in all investigated recombinant Mbs, indicating a conserved structure. The highest O2 affinity was measured for PanMb2 (P50 = 0.88 Torr at 20 °C), which is mainly expressed in the brain, whereas the muscle‐specific PanMb1 has the lowest O2 affinity (P50 = 3.78 Torr at 20 °C), suggesting that tissue‐specific O2 requirements have resulted in the emergence of distinct Mb types. Two of the mainly neuronally expressed Mbs (PanMb3 and PanMb4b) have the highest nitrite reductase rates. These data show different O2 binding and enzymatic properties of lungfish Mbs, reflecting multiple subfunctionalisation and neofunctionalisation events that occurred early in the evolution of lungfish. Some Mbs may have also taken over the functions of neuroglobin and cytoglobin, which are widely expressed in vertebrates but appear to be missing in lungfish. Abstract : The lungfish harbors multiple copies of the oxygen‐binding protein myoglobin (Mb). Amplification of this gene occurred during an early stage of lungfish evolution. The Mbs are differentially expressed throughout various tissues and display different abilities to bind oxygen or act as enzymes. Remarkably, the main expression site of the Mbs is the brain and not the name‐giving muscle.